Determination of some biochemical parameters in sera of normotensive and hypertensive obese female in Baghdad. Issue 1 (March 2021) - Taay, Y M; Mohammed, M T; Abbas, R; Ayad, A; Mahdi, M A
Abstract: Obesity is a disease describe a case of excessive accumulation of body fats. Obesity is linked to the morbidity of human health, such as the development of hypertension. The study designed to investigate the levels of glucose, urea, creatinine, and lipid profile parameters in sera of obese female and hypertensive obese female. The study included 90 subjects who divided onto three groups equally, in which they are healthy control, normotensive obese, and hypertensive obese. A significant elevation (P<0.01) has observed in the level of glucose, urea, creatinine, triglycerides (TGs), cholesterol, LDL-C, and VLDL-C in obese females compared with control, yet only TGs and VLDL-C were significantly differ in hypertensive obese from normotensive obese. On the other hand the level of HDL-C was significantly decreased in obese female compared with control. The elevation of TGs and VLDL in hypertensive obese female indicates their role in the complications of hypertension during obesity.